Single dose of intra-muscular platelet rich plasma reverses the increase in plasma iron levels in exercise-induced muscle damage: A pilot study - Zekine Punduk; Onur Oral; Nadir Ozkayin; Khalid Rahman; Rana Varol (Elsevier, 2016)
Background: Platelet rich plasma (PRP) therapy is widely used in enhancing the recovery of skeletal muscle from injury. However, the impact of intramuscular delivery of PRP on hematologic and biochemical responses has not been fully elucidated in exercise-induced muscle damage. The purpose of this investigation the effects of intramuscular delivery of PRP on hematologic and biochemical responses and recovery strategy muscle damage induced by high intensity muscle exercise (exercise-induced muscle damage, EIMD). Methods: Moderately active male volunteers participated in this study and were assigned to a control group (control, n = 6) and PRP administration group (PRP, n = 6). The subjects performed exercise with a load of 80% one repetition maximum (1RM) maximal voluntary contraction of the elbow flexors until point of exhaustion of the non-dominant arm was reached. The arms were treated with saline or autologous PRP post-24 h EIMD. Venous blood samples were obtained in the morning to establish a baseline value and 1-4 days post-exercise and were analyzed for serum ferritin, iron, iron binding capacity (IBC), creatinine kinase (CK), lactate dehydrogenase (LDH), aspartate aminotransferase (AST), and alanine aminotransferase (ALT). Results: The baseline levels of plasma iron, ferritin, IBC, CK, LDH, AST, and ALT were similar in both the control and PRP groups. However, 24-h following exercise a significant increase in these parameters was observed in both groups between 1 and 4 days during the recovery period. Interestingly, PRP administration decreased plasma iron levels compared to the control on the second day post-exercise. Plasma IBC increased in PRP group from Days 2 to 4 post-exercise compared to the control group whilst PRP administration had no effect on plasma ferritin, CK, AST, ALT, or LDH. Conclusion: Acute exhaustive exercise increased muscle damage markers, including plasma iron, IBC, and ferritin levels, indicating muscle damage induced by exercise. PRP administration improves inflammation by reversing the increase in the iron levels post-exercise without displaying any myotoxicity and may have a role to play in the recovery of exercise-induced muscle damage.